AN APPRAISAL OF FACTORS AFFECTING CASH FLOW’S IN BUILDING PROJECT DELIVERY IN NIGERIA - Usman, Nuruddeen; Sani, Abdulkadir; Tukur, Rukayya Ibrahim (IJRDO - Journal of Applied Management Science, 2016)
Appropriate cash planning techniques is necessary for adequate cost control and efficientcash management. Contractors cannot survive in the competitive environment withouteffective cash flow management. However, cash flow is the lifeline of project delivery,deficiency in cash flow may cause failure of the project. Therefore, this study aimed atassessing the contractor’s cash flows effect on the delivery of projects in Nigeria. Thus,Explorative and questionnaire survey methods used to obtained data from literature andconstruction professionals. Data obtained were analysed using SPSS for descriptive statisticssuch as mean score and percentages. The findings of the study show that, delay payment(AMS=3.92), delay in settling of claims (AMS=3.88), loan repayment (AMS=3.87),consultant instruction (AMS= 3.82) and change in interest rate (AMS=3.77) are the mainfactors that are affecting cash flow on projects delivery in Nigeria.Hence, contractors shouldembark on project for which they have adequate fund to execute and all the claims madeshould be guinea and finally, client should honour certificate of payment as when due toavoiding improper funding of projects as well as settling verified claims within a reasonabletime frame of the projects duration.